Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1029/2003gl017221
|View full text |Cite
|
Sign up to set email alerts
|

The carbon kinetic isotope effects of ozone‐alkene reactions in the gas‐phase and the impact of ozone reactions on the stable carbon isotope ratios of alkenes in the atmosphere

Abstract: [1] The kinetic isotope effects (KIEs) for several ozonealkene reactions in the gas phase were studied in a 30 L PTFE reaction chamber. The time dependence of the stable carbon isotope ratios and the concentrations were determined using a gas chromatography combustion isotope ratio mass spectrometry (GCC-IRMS) system. The following average KIE values were obtained: 18.9 ± 2.8 (ethene), 9.5 ± 2.5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 12 publications
2
46
0
Order By: Relevance
“…There is also a more theoretical implication. While the previously reported value suggested that the KIE for the reaction of isoprene fits well into the semi-empirical relationship between KIE and number of carbon atoms derived by Iannone et al (2003) for reactions of alkenes with ozone, the new KIE is (1.4±0.3) ‰ higher than the prediction.…”
Section: Comparison With Previously Published Datamentioning
confidence: 41%
See 3 more Smart Citations
“…There is also a more theoretical implication. While the previously reported value suggested that the KIE for the reaction of isoprene fits well into the semi-empirical relationship between KIE and number of carbon atoms derived by Iannone et al (2003) for reactions of alkenes with ozone, the new KIE is (1.4±0.3) ‰ higher than the prediction.…”
Section: Comparison With Previously Published Datamentioning
confidence: 41%
“…The new KIE for isoprene is with (8.40 ± 0.11) ‰ somewhat higher than the previously reported value of (6.1 ± 1.0) ‰ (Iannone et al, 2003). This value is an average of four measurements ranging from 4.0-7.8‰, resulting in a 95% confidence interval of 2.84-7.79‰.…”
Section: Comparison With Previously Published Datamentioning
confidence: 50%
See 2 more Smart Citations
“…3,4 Rudolph et al 5 also described a kinetic fractionation effect on the stable carbon isotopes of organic compounds during the oxidation by OH radicals in the atmosphere, similar to the study by Iannone et al for ozone. 6 This isotope effect can be used to study the different processes that contribute to the atmospheric concentration of carbonaceous aerosols. However, only little information is available on the stable carbon isotopic composition of carbonaceous aerosols and their gas-phase counterparts in the atmosphere.…”
mentioning
confidence: 99%